Crosstalk of the Insulin-Like Growth Factor Receptor with the Wnt Signaling Pathway in Breast Cancer - Rota, Lauren M.; Wood, Teresa L. (Frontiers in Endocrinology, 2015)
The insulin-like growth factor system has long been considered a pathway that promotes cell proliferation, survival and transformation and is thus a promoter of tumorigenesis. However, recent failure of clinical trials for IGF-1R inhibitors reveals the need for a better understanding of how this pathway functions in specific tumor subtypes. Ongoing studies are designed to uncover biomarkers and downstream targets to enhance therapeutic strategies. Other approaches in specific tumor models reveal complex interactions between IGF signaling and other tumor initiating pathways. Here we review relevant background and recent studies suggesting that inhibiting the IGF-1R can amplify Wnt and Notch signaling pathways in a model of triple negative breast cancer.